KAPASITAS ADSORPSI ARANG AKTIF CANGKANG BINTARO (Cerbera odollam) TERHADAP ZAT WARNA SINTETIS REACTIVE RED-120 DAN REACTIVE BLUE-198 - Siti Zaya Aisyahlika; M. Lutfi Firdaus; Rina Elvia (ALOTROP, 2018)
The objective of this research was to utilize bintaro shell waste (Cerbera odollam). The morphology of bintaro shell is similar with coconut shell and the contains of lignin and cellulose is higher than coconut. Bintaro shell waste used as activated charcoal to remove environmental pollution caused by synthetic dyes waste of batik industry. The adsorbents were then applied to remove of Reactive Red-120 (RR) and Reactive Blue-198 (RB) dyes in aqueous solution using Visible Spectrophotometer analysis method. Bintaro shell was dried, cut and carbonized at 400°C for 1 hour, then activated with ZnCl2 20% for 24 hours at 27°C and dryed in oven at 105°C for 30 minutes. The activated charcoal of bintaro shell has proven afford to adsorbing RR and RB dyes. The optimum conditions (pH, contact time, adsorbent weight and temperature) were determined to obtain best adsorption capacity. The optimum of conditions for RR occured at pH 2, contact time of 40 minutes and adsorbent weight 100 mg while RB occurred at pH 11, contact time of 60 minutes and adsorbent weight 50 mg and with each the temperature 30°C. At optimum conditions the adsorption isotherm followed Freundlich model with maximum adsorption capacity obtained for RR and RB were 332.6 and 243.9 mg/g, respectively.